BAG2-activated cell autophagy and mir-27b dynamic regulation mechanism during Mycobacterium tuberculosis infection - Xing, Xiaoming; Zhang, Cuiyun; Zhou, Jie; Jin, Qian; Zheng, Qinfang (Cellular and Molecular Biology, 2022)
Tuberculosis is a highly contagious infectious disease. Mycobacterium tuberculosis infection is the main cause of tuberculosis. During the infection of M. tuberculosis, the expression of the resistance gene BAG2 will change, and miR-27b will play a certain role in dynamic regulation. The purpose of this article is to explore in-depth the effect of BAG2 on cell autophagy during M. tuberculosis infection and the dynamic regulatory mechanism of miR-27b on BAG2 activated cell autophagy. Fifty rats were used as experimental subjects, and M. tuberculosis strains H37Ra and H37Rv were implanted into the rats. Fluorescence quantitative PCR was used to detect the dynamic changes of BAG2 and miR-27b expression levels in rats and the regulatory effect of miR-27b on BAG2, and the effect of changes in BAG2 expression levels on cell autophagy was studied by immunoblotting. The results showed that after M. tuberculosis-infected macrophages, the expression level of BAG2 decreased from (284.24±6.31) to (156.48.24±4.49), and the expression level of miR-27b was increased from (43.72±3.35) to (78.35± 4.17), the apoptosis rate increased by 17.8%, and the autophagy rate increased by 20.6%. Therefore, it can be seen that the up-regulation of miR-27b expression level during M. tuberculosis infection will inhibit BAG2 expression, thereby promoting cell autophagy and apoptosis to reduce the survival rate of M. tuberculosis.